2011
DOI: 10.1182/blood-2009-07-234310
|View full text |Cite
|
Sign up to set email alerts
|

Evi-1 is a transcriptional target of mixed-lineage leukemia oncoproteins in hematopoietic stem cells

Abstract: Ecotropic viral integration site-1 (Evi-1) is a nuclear transcription factor that plays an essential role in the regulation of hematopoietic stem cells. Aberrant expression of Evi-1 has been reported in up to 10% of patients with acute myeloid leukemia and is a diagnostic marker that predicts a poor outcome. Although chromosomal rearrangement involving the Evi-1 gene is one of the major causes of Evi-1 activation, overexpression of Evi-1 is detected in a subgroup of acute myeloid leukemia patients without any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 51 publications
2
79
2
Order By: Relevance
“…25 Although others reported binding of MLL-ENL to the Evi1 promoter, we were not able to show direct interaction between MLL-AF9 and Evi1, possibly because of the lack of suitable ChIP-grade Abs. However, we observed clear differences between Evi1 pos and Evi1 neg MLL-AF9-transformed cells (both human or mouse) with regard to enrichments of H3K79/H3K4 versus H3K27 on the EVI1 promoter.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations
“…25 Although others reported binding of MLL-ENL to the Evi1 promoter, we were not able to show direct interaction between MLL-AF9 and Evi1, possibly because of the lack of suitable ChIP-grade Abs. However, we observed clear differences between Evi1 pos and Evi1 neg MLL-AF9-transformed cells (both human or mouse) with regard to enrichments of H3K79/H3K4 versus H3K27 on the EVI1 promoter.…”
Section: Discussioncontrasting
confidence: 73%
“…These results are corroborated by recent reports showing that MLL-ENL up-regulates Evi1 expression in a mouse leukemia model, in which leukemic transformation was dependent on Evi1. 24,25 We noted that although MLL-AF9 is readily able to transform normal mouse BM cells, only a fraction of colonies were Evi1 pos (supplementary figure S5B). Similar to Arai et al, we found that in these retroviral models of MLL-fusion gene leukemia, Evi1 overexpression was predominantly associated with the stem cell-enriched LSK raction of normal BM compared with the more differentiated myeloid progenitors CMP, GMP, and MEP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…81 Something similar had been shown before for Evi1 (ref. 82) and also, importantly in the case of MLL fusion genes, for Hox genes like Hoxa9 (ref. 83).…”
Section: Mll-involving Translocations-based Gemmsmentioning
confidence: 99%